Study of plasma sheath in the presence of dust particles in a magnetic mirror-like field configuration. (14th March 2023) - Deka, K; Sharma, G; Paul, R; Moulick, R; Adhikari, S; Kausik, S S; Saikia, B K
Abstract: The properties of a plasma sheath in the presence of dust grains and a magnetic mirror-like field configuration have been investigated in this study. All the plasma species viz. electrons, ions, and dust grains are described by fluid equations. The system of equations involved in the study is solved numerically using the Runge-Kutta fourth-order (RK4) method to explore the sheath properties. The results of the study suggest that in the presence of a magnetic mirror-like field configuration, the component of ion velocity perpendicular to the wall decreases near the surface, and consequently, the ion density increases. To the best of our knowledge, such observations have not been reported anywhere previously. This utterly different observation is due to the magnetic field configuration alone. Such a behavior can be used to control the dynamics of the ions in the sheath. Moreover, ion-neutral collisions tend to reduce the effect of the magnetic field on the properties of the sheath. The study may be helpful to understand the interactions of plasma with the wall in different plasma-assisted industrial applications containing dust grains as contaminants. Besides, the study will play a significant role in controlling the dynamics of positive ions and negatively charged dust grains in the sheath. The space charge shows an unusual behavior near the sheath. In the usual scenario, the space charge slightly decreases near the wall. But in the present context, the space charge increases. Further, it has been observed that the dust surface potential near the wall becomes less negative with the increase in magnetic field strength. The magnetic field and ion-neutral collisions tend to restrict the movement of the ions toward the wall when acting separately, but their combined effect leads to a different kind of behavior altogether.